Homoacetogenesis competes with hydrogenotrophic methanogenesis for substrates in a peatland experiencing ecosystem warming. (September 2022) - LeeWays, Cory; McCullough, Laura L.; Hopple, Anya M.; Keller, Jason K.; Bridgham, Scott D.
Abstract: Peatlands contain up to half of terrestrial soil organic carbon (C) while simultaneously emitting the potent greenhouse gas methane (CH4 ). Global change will alter C biogeochemistry in peatlands, but is hard to predict without a mechanistic understanding of the processes that control anaerobic C cycling. One of the least known anaerobic C cycling pathways in wetland systems is homoacetogenesis, the reduction of carbon dioxide (CO2 ) with dihydrogen (H2 ) to acetate. We developed a new technique to infer rates of putative homoacetogenesis by measuring the incorporation of 14 C-labeled dissolved inorganic C into dissolved organic matter. We determined rates of homoacetogenesis and total and hydrogenotrophic CH4 production throughout the peat profile on two sampling dates in a whole-ecosystem warming and elevated CO2 experiment in a northern Minnesota bog, USA. Homoacetogenesis and hydrogenotrophic CH4 production were greatest in surface soils and at warmer temperatures. However, homoacetogens were stronger competitors than hydrogenotrophic methanogens for H2 in deeper soil depths and at lower temperatures. A higher ratio of acetoclastic to hydrogenotrophic methanogenesis is often associated with greater total CH4 production, indicating that homoacetogenesis potentially can indirectly increase total CH4 production. Additionally, failure to account for homoacetogenesis may lead to erroneous conclusions in stable isotope models of anaerobic C cycling and CH4 production. This work shows that homoacetogenesis responds to warming and may impact CH4 production, and thus this process should be included in future modeling of climate change effects in wetlands. Highlights: Homoacetogenesis is rarely studied but potentially important in natural ecosystems. We developed a new method to quantify putative homoacetogenesis. Homoacetogenesis competed with hydrogenotrophic methanogenesis for H2 in a wetland. Temperature and peat depth affected the degree of this competition.